Twentieth-century sentimentalism : narrative appropriation in American literature - Williamson, Jennifer A., 1978- (Rutgers University Press, 2014)
"Today's critical establishment assumes that sentimentalism is an eighteenth- and nineteenth-century literary mode that all but disappeared by the twentieth century. In this book, Jennifer Williamson argues that sentimentalism is alive and well in the modern era. By examining working-class literature that adopts the rhetoric of "feeling right" in order to promote a proletarian or humanist ideology as well as neo-slave narratives that wrestle with the legacy of slavery and cultural definitions of African American families, she explores the ways contemporary authors engage with familiar sentimental clichés and ideals. Williamson covers new ground by examining authors who are not generally read for their sentimental narrative practices, considering the proletarian novels of Grace Lumpkin, Josephine Johnson, and John Steinbeck alongside neo-slave narratives written by Margaret Walker, Octavia Butler, and Toni Morrison. Through careful close readings, Williamson argues that the appropriation of sentimental modes enables both sympathetic thought and systemic action in the proletarian and neo-slave novels under discussion. She contrasts appropriations that facilitate such cultural work with those that do not, including Kathryn Stockett's novel and filmThe Help. The book outlines how sentimentalism remains a viable and important means of promoting social justice while simultaneously recognizing and exploring how sentimentality can further white privilege. Sentimentalism is not only alive in the twentieth century. It is a flourishing rhetorical practice among a range of twentieth-century authors who use sentimental tactics in order to appeal to their readers about a range of social justice issues. This book demonstrates that at stake in their appeals is who is inside and outside of the American family and nation."--JSTOR website (viewed April 18. 2017).